Evolution of mammalian migrations for refuge, breeding, and food. Issue 15 (22nd June 2017) - Gnanadesikan, Gitanjali E.; Pearse, William D.; Shaw, Allison K.
Abstract: Many organisms migrate between distinct habitats, exploiting variable resources while profoundly affecting ecosystem services, disease spread, and human welfare. However, the very characteristics that make migration captivating and significant also make it difficult to study, and we lack a comprehensive understanding of which species migrate and why. Here we show that, among mammals, migration is concentrated within Cetacea and Artiodactyla but also diffusely spread throughout the class (found in 12 of 27 orders). We synthesize the many ecological drivers of round‐trip migration into three types of movement—between breeding and foraging sites, between breeding and refuge sites, and continuous tracking of forage/prey—each associated with different traits (body mass, diet, locomotion, and conservation status). Our results provide only partial support for the hypothesis that migration occurs without phylogenetic constraint. Furthermore, our findings suggest that categorizing migration into these three types may aid predictions of migrants' responses to environmental changes. Abstract : Although many organisms migrate annually between distinct habitats, we currently lack a comprehensive understanding of which species migrate and why. Here, we show that, among mammals, migration is concentrated within Cetacea and Artiodactyla but also diffusely spread throughout the class, providing only partial support for the hypothesis that migration occurs without phylogenetic constraint. We also synthesize the many ecological drivers of round‐trip migration into three types of movement, each associated with different traits, suggesting that this categorization may aid predictions of migrants' responses to environmental changes.